SOLDADOR, O ARTESÃO DA INDÚSTRIA NAVAL OFFSHORE: UMA DISSERTAÇÃO SOBRE O CONHECIMENTO - Bassani, Denise Terezinha Lisboa (2006)
The present research aims to understand and explore disorders in final results in the welders works in the naval / offshore on a case study basis concerning a typical organization through the analysis statements collected from various professionals in different levels of qualification / competences, comparing and seeking explanations for such disorders along theories about the knowledge production, particularly the relationship and complementarity between the tacit and explicit knowledge. A theoretical comprehension about the phenomenon allows to propose / establish directives for elaboration of training politics comprehending the selection / qualification stage so to minimize costs due to disharmony between theory and practice into a sector as welding, where the process technical complexity is high and the consequences of errors show problematic propagation throughout the whole productive process.